2014
DOI: 10.1021/jp503422c
|View full text |Cite
|
Sign up to set email alerts
|

Putative Hydrogen Bond to Tyrosine M208 in Photosynthetic Reaction Centers from Rhodobacter capsulatus Significantly Slows Primary Charge Separation

Abstract: Slow, ∼50 ps, P* → P+HA– electron transfer is observed in Rhodobacter capsulatus reaction centers (RCs) bearing the native Tyr residue at M208 and the single amino acid change of isoleucine at M204 to glutamic acid. The P* decay kinetics are unusually homogeneous (single exponential) at room temperature. Comparative solid-state NMR of [4′-13C]Tyr labeled wild-type and M204E RCs show that the chemical shift of Tyr M208 is significantly altered in the M204E mutant and in a manner consistent with formation of a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 93 publications
3
19
0
Order By: Relevance
“…Complex kinetics were also found for P* → P + B A − → P + H A − and P + H A − → P + Q A − in WT RCs, implying multiple populations (4,37). P* populations that exhibit different photochemistry, such as seen here, also have been described for various mutants (9,33,44,62). These findings, the data here, and the model in Fig.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Complex kinetics were also found for P* → P + B A − → P + H A − and P + H A − → P + Q A − in WT RCs, implying multiple populations (4,37). P* populations that exhibit different photochemistry, such as seen here, also have been described for various mutants (9,33,44,62). These findings, the data here, and the model in Fig.…”
supporting
confidence: 82%
“…Both theory and experiments have shown that TyrM210 is key to positioning P + B A − slightly (∼70 meV) below P* in free energy, while symmetry-related PheL181 does not provide such stabilization of P + B B − , which is thought to be ∼100 to 200 meV above P* (Figs. 1 and 2A) (6)(7)(8)(9)(10)(11)(12)(13). State P + H B − also is higher in free energy than its A-side counterpart (P + H A − ) and may be only ∼70 meV below P* (14).…”
mentioning
confidence: 96%
“…For instance, the tyrosine at M210 (Figure 1) has long been indicated as a key factor for L-branch electron transfer because it is a clear deviation in symmetry between the L and M branch protein environments, and it is the only 1 out of the 28 tyrosines in the RC whose hydroxyl group is not hydrogen-bonded. 6 Past simulation results have indicated that the orientation and dipole of the tyrosine hydroxyl play an important role in stabilizing initial charge transfer intermediates. 7 Recent results from our lab demonstrated the impact of introducing a putative hydrogen bond partner near Y(M210), a change which could reorient the tyrosine −OH dipole away from maximally stabilizing interactions for charge transfer indicated by these simulation results.…”
mentioning
confidence: 73%
“…Despite the significant energetic impact of some ncAAs, no tyrosine modification made an order of magnitude impact on the overall rate (5,10,31,72) or yield (27) of ET, highlighting the robust nature of the RC's protein design (1,(4)(5)(6)(7)(8)(9)(10)(11). This small overall effect may be a consequence of this dualmechanism model, where the superexchange mechanism is acting as an alternative functional pathway for ET as previously proposed in the literature (19) through a lowered sensitivity to energetic changes of the P + BAintermediate.…”
Section: Discussionmentioning
confidence: 60%
“…Theoretical studies indicates that the magnitude and orientation of the hydroxyl dipole of tyrosine M210 may play an important role in energetically stabilizing P + BA - (29,30). Indeed, previous efforts to change the orientation of this tyrosine's hydroxyl dipole significantly slowed ET (31). It is difficult, however, to subtly vary the electrostatic nature of this tyrosine using canonical mutagenesis without entirely removing the phenolic hydroxyl.…”
Section: Introductionmentioning
confidence: 99%